Atatürk’ün Halkçılık Politikasında Köycülüğün Yeri ve Antalya Halkevi’nin Solak Köyü’nde Yaptığı Örnek Köy Çalışması - Nursel GÜLCÜ (Gazi Akademik Bakış)
M. Kemal Ataturk ultimately managed all the works in the young republic to raise a modern state grounded on the principle of populism. In this newly established state, spreading the idea of a “republic” was considered key to success. Considering that the majority of the citizens dwelled in villages at those times, it was expected to develop the village in every aspect. Ataturk enacted numerous laws to promote the development of the villages and exerted great efforts for people, particularly villagers, to adopt the innovations. In this regard, Ataturk led the opening of People’s Houses (Community Centers) in 1932 to initiate significant cultural development throughout the country. He also closely followed the activities of these centers, which became widespread in many parts of Turkey in a short time, supported their activities, and insisted on implementing the activities within a specific program. In particular, he wished the Peasantry Branches of People’s Houses to carry out activities actively in the villages. Antalya People’s Houses, opened in 1932, also carried out activities aiming to develop villages in Antalya within this policy through its Peasantry Branch. This branch mainly chose some villages and attempted to implement its program in these villages in the scope of “model village” practice. The branch prepared a model village program for Solak village, among the sample villages, and carried out the designated activities in the village within this program. The present study discussed the practices implemented in Solak village by the Peasantry Branch of Antalya People’s House in the framework of Ataturk’s populism policy and attempted to reveal the projections and recognition of the practices carried out at those times in the present of Solak village.